Benefits of Cultural Activities on People With Cognitive Impairment: A Systematic Review - Delfa-Lobato, Laia; Guàrdia-Olmos, Joan; Feliu-Torruella, Maria (Frontiers in Psychology, 2021)
Museums and cultural institutions are increasingly striving to respond to the interests and needs of the society that hosts them. This means, apart from other actions, that these institutions must be involved in the health and well-being of society and the creation of cultural activities aimed at people with cognitive impairment, a group of individuals that is growing worldwide due to the aging of society and the increasing prevalence of dementia. The involved sectors are aware of the potential and benefits of activities for this population, even though there is much research to be conducted. To date, no systematic review has focused on the benefits of cultural activities for cognitively impaired people. This study aimed to explore the benefits of different modalities of cultural activities with evidence from 145 studies from various databases, which met the inclusion criteria. Significant improvements in general cognition, quality of life, emotional well-being, socialization, and communication were generally reported after interventions, with a reduction in depression symptoms. There was not enough evidence to prove memory, language, or daily functioning improvements attributable to cultural interventions. There were no significant reductions reported in apathy, sadness, agitation, or anxiety.